Kentucky Agricultural Education Teachers’ Self-reported Percentages of Mathematics Content within Secondary Agricultural Education Curricula - Wells, Trent; Anderson, Ryan G. (Journal of Agricultural Systems, Technology, and Management, 2015)
The mathematics achievement of secondary students in American schools is, to say the least, shocking. In addition, as the need for a more competent workforce in the agricultural industry has emerged, the agricultural education profession has taken up the charge of preparing individuals who are capable of solving tomorrow’s complex agricultural issues. A portion of this response has been contextually teaching mathematics through agricultural education coursework. However, a question has emerged: Are agricultural education teachers in Kentucky adequately utilizing mathematics content within their curricula? The researchers utilized a modified version of Anderson’s (2006) instrument to address the research objectives. Eighty-nine Kentucky agricultural education teachers participated in this study. The researchers found that mathematics content utilization within Kentucky agricultural education coursework is, at the moment, somewhat limited. The Advanced Agricultural Economics & Agribusiness Management course indicated the highest percentage of mathematics content while the Agricultural Power, Structures, & Technical Systems career pathway reported the highest percentage of mathematics. Perhaps agricultural education teachers vary in their working definitions of mathematics content integration. Additional research should further examine mathematics content integration as applied to the context of agricultural education.